Location, location, location: Extracting location value from house prices - Jens Kolbe; Rainer Schulz; Martin Wersing; Axel Werwatz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We propose a novel semiparametric method to extract location values from house prices. After splitting house prices into building and land components, location values are estimated with adaptive weight smoothing. The adaptive estimator requires neither strong smoothness assumptions nor local symmetry. We apply the method to house transactions from Berlin, Germany. The estimated surface of location values is highly correlated with expert-based land values and location ratings. The method can therefore be used for applications where no other location value information exists or where this information is not reliable.
Keywords: C14; R31; C50; 330